2019
DOI: 10.1186/s43043-019-0005-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vitamin D supplementation on cardio-metabolic status and androgen profile in women with polycystic ovary syndrome: placebo-controlled clinical trial

Abstract: Background Polycystic ovary syndrome (PCOS) is a heterogeneous disorder of reproductive, endocrine, and metabolic functions. Vitamin D has an influence on metabolic and reproductive functions. This study was designed to explore the levels of free 25 hydroxycholecalciferol [25(OH)-D] in PCOS patients. We also aimed to clarify the impact of vitamin D supplementation on cardio-metabolic status, androgen profile, and clinical features of PCOS. Results Our results revealed significant lower levels of serum 25(OH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 42 publications
0
15
1
Order By: Relevance
“…In agreement with our results, Rashad et al showed that VD 3 level was negatively correlated with free testosterone. 17 In contrast to our results, Arslan et al demonstrated that AMH levels were not correlated with 25(OH)D levels in PCO group. 18 This may be contributed to different ethnic group or geographical factors or different lifestyle.…”
Section: Discussioncontrasting
confidence: 99%
“…In agreement with our results, Rashad et al showed that VD 3 level was negatively correlated with free testosterone. 17 In contrast to our results, Arslan et al demonstrated that AMH levels were not correlated with 25(OH)D levels in PCO group. 18 This may be contributed to different ethnic group or geographical factors or different lifestyle.…”
Section: Discussioncontrasting
confidence: 99%
“…Rashad et al found that the clinical manifestations, metabolic indices, and androgenic aspects of PCOS have improved. Body composition measures, BMI, and waist-hip ratio all decreased significantly in the intervention group [17]. Furthermore, after getting vitamin D3 medication, cardio-metabolic risks were reduced, and a novel finding in this clinical trial was a reduction in pro-inflammatory biomarkers.…”
Section: Resultsmentioning
confidence: 63%
“…This is due to the limited ability of immunoassays to accurately quantify low levels of testosterone, cross-reactivity with steroid metabolites, precursors and conjugates, and regular changes in proprietary assay reagents [26]. Additionally, some of these studies have also failed to adjust for important confounders such as insulin resistance and/or BMI [7,8,27], which are often elevated in an individual's PCOS, and directly affect androgens [28,29]. However, we saw no correlations between vitamin D components and androgens even before adjustment for these confounders.…”
Section: Discussionmentioning
confidence: 99%